DEFORMATION PROPERTIES OF RUBBERISED CONCRETE MODIFIED WITH STEEL TYRE WIRE - R RAVICHANDRAN, THEVAKARAN (Universiti Teknologi PETRONAS, 2020)
The implementation of producing rubberized concrete was initiated due to increase in number of waste tyres as the automobile industry is growing exponentially as well as the incapability of the tyres to degrade in their natural conditions. This challenges subsequently brought the idea of incorporation of waste tyres in the construction industry which proven to be an effective method to dispose the end-of-life tyres. The waste tyres will be converted into crumb rubber which will be utilized as a partial substitute of fine aggregates in concrete mix. Rubberized concrete is commonly utilized in the construction industry for road engineering, railway tracks, bridges. However, the compressive strength, elasticity modulus of the rubberized decreases as the amount of rubber in the concrete increases compared to the conventional concrete. Thus, the rubberized concrete is not utilized for structural application.